2017
DOI: 10.1186/s40854-017-0073-x
|View full text |Cite
|
Sign up to set email alerts
|

Financial sector development and economic growth: evidence from Cameroon

Abstract: For decades, African economies have embarked on financial sector reforms. However, the empirical implications of these reforms have been divergent. This paper investigates the impact of financial development on Economic growth using time series data in Cameroon. This investigation was carried out using three common indicators of financial development (broad money, deposit/GDP and domestic credit to private sector). Using the Auto Regressive Distributive Lag (ARDL) technique of estimation, it was discovered tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 44 publications
7
43
0
Order By: Relevance
“…The results of this work can provide policy direction for other fast-growing developing countries that would like to attract FDI. This paper also complements recent literature that has focused on factors determining investment in developing countries, including Bartels et al (2009), Tuomi (2011), Kolstad and Wiig (2011), Darley (2012), Asongu (2012Asongu ( , 2013bAsongu ( , 2013cAsongu ( , 2015, Ajide and Raheem (2016), Xiong et al (2015), Safaee and Geray (2017), and Pautwoe and Piabuo (2017).…”
Section: Introductionsupporting
confidence: 58%
“…The results of this work can provide policy direction for other fast-growing developing countries that would like to attract FDI. This paper also complements recent literature that has focused on factors determining investment in developing countries, including Bartels et al (2009), Tuomi (2011), Kolstad and Wiig (2011), Darley (2012), Asongu (2012Asongu ( , 2013bAsongu ( , 2013cAsongu ( , 2015, Ajide and Raheem (2016), Xiong et al (2015), Safaee and Geray (2017), and Pautwoe and Piabuo (2017).…”
Section: Introductionsupporting
confidence: 58%
“…The result is consistent with those of Adediran (2017), Paul (2017), Puatwoe and Piabuo (2017), Ndako (2017) who also reported that financial development significantly impacted on economic growth and that credit to private sector has material impact on economic growth. Indeed, it upholds the findings of Jalil & Ma, (2008) that financial development measured as loan-deposit ratio and credit to private sector have significant positive influence the economy development of Pakistan.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…By using ARDL approach Inheanacho (2016), found that insignificantly negative in the long run and significantly negative in the short run in Nigeria over the period 1981-2011. Similar study was conducted by Puatwoe and Piabuo (2017) found that in short run, broad money, government expenditure and economic growth have positive relationship. Meanwhile, all indicators show potive impact and significantly on economic growth in Camerron from 1980-2014.…”
Section: Introductionsupporting
confidence: 69%